Evaluating the Effectiveness of Telemedicine in Managing Common Conditions in Family Medicine: Telemedicine Outcomes in Family Medicine - Siddiqui, Nimra; Zaki, Noor Ul Huda; Samir, Komal; Khalid, Unaiza; Khawaja, Naveen; Ahsan, Shaharyar (Pakistan Journal of Health Sciences, 2025)
Telemedicine has been progressively implemented worldwide for managing common presentations in family medicine, a cornerstone of primary care. Its implementation has accelerated since the COVID-19 pandemic, offering improved healthcare access, cost-effectiveness, reduced hospital visits, and better clinical outcomes. Objectives: To evaluate the effectiveness of telemedicine in managing common conditions in family medicine. Methods: This systematic review was performed in accordance with PRISMA guidelines. An electronic search of PubMed, Google Scholar, and Science Direct databases was performed for papers published from January 2014 until December 2023. We included studies in English that measured telemedicine efficacy among common acute or chronic conditions in the family medicine setting. Results: In the 14 trials included, telemedicine successfully managed a variety of common conditions. Aggregate outcomes revealed that readmission to hospitals among patients with heart failure was significantly decreased, better clinical status in diabetes and obesity, including diet habits, BMI enzymion and blood pressure. Conclusions: Telemedicine is an effective tool for managing common conditions encountered in family medicine, boosting care access, cost-efficiency, and clinical outcomes. Targeting the development of evidence-based guidelines for hybrid care models and evaluations of long-term effects on chronic disease outcomes, research is needed.